2010
DOI: 10.1104/pp.109.151738
|View full text |Cite
|
Sign up to set email alerts
|

R2R3-NaMYB8 Regulates the Accumulation of Phenylpropanoid-Polyamine Conjugates, Which Are Essential for Local and Systemic Defense against Insect Herbivores inNicotiana attenuata

Abstract: Although phenylpropanoid-polyamine conjugates (PPCs) occur ubiquitously in plants, their biological roles remain largely unexplored. The two major PPCs of Nicotiana attenuata plants, caffeoylputrescine (CP) and dicaffeoylspermidine, increase dramatically in local and systemic tissues after herbivore attack and simulations thereof. We identified NaMYB8, a homolog of NtMYBJS1, which in BY-2 cells regulates PPC biosynthesis, and silenced its expression by RNA interference in N. attenuata (ir-MYB8), to understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
312
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 220 publications
(324 citation statements)
references
References 103 publications
11
312
1
Order By: Relevance
“…Accumulating evidence shows that PAs play an important role in plant defense responses against pathogens and insect herbivores (Newman et al, 2001;Tanaka et al, 2003;Kaur et al, 2010;Park et al, 2014). They are also suggested to play roles in sulfur starvation, heat shock, and protection against UV irradiation (Klapheck, 1983;Edreva et al, 1998;Kaur et al, 2010), although clear evidence to support these roles is yet to be reported (Fellenberg and Vogt, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence shows that PAs play an important role in plant defense responses against pathogens and insect herbivores (Newman et al, 2001;Tanaka et al, 2003;Kaur et al, 2010;Park et al, 2014). They are also suggested to play roles in sulfur starvation, heat shock, and protection against UV irradiation (Klapheck, 1983;Edreva et al, 1998;Kaur et al, 2010), although clear evidence to support these roles is yet to be reported (Fellenberg and Vogt, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…PAs are a diverse group of specialized metabolites found in many plants, including wheat (Triticum aestivum), barley (Hordeum vulgare), rice (Oryza sativa), and maize (Zea mays) (Martin-Tanguy et al, 1978;Martin et al, 1985;Facchini et al, 2002;Edreva et al, 2007;Bassard et al, 2010). Accumulating evidence shows that PAs play an important role in plant defense responses against pathogens and insect herbivores (Newman et al, 2001;Tanaka et al, 2003;Kaur et al, 2010;Park et al, 2014). They are also suggested to play roles in sulfur starvation, heat shock, and protection against UV irradiation (Klapheck, 1983;Edreva et al, 1998;Kaur et al, 2010), although clear evidence to support these roles is yet to be reported (Fellenberg and Vogt, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of this study, we first used three transgenic lines produced in the U30 background and in which phenolamide metabolism is affected. When stably silencing MYB8 (irMYB8), a transcription factor that controls total phenolamide production (28,29), both N-caffeoylputrescine and unknown at m/z 347 disappeared from the extract ion current chromatograms (Fig. 5D).…”
Section: Navigating the Idms/ms Molecular Network Facilitates Structumentioning
confidence: 99%
“…S10), provided additional support that this unknown was related to putrescine-based phenolamide metabolism. N-caffeoylputrescine is a prominent defense compound in N. attenuata (29), and understanding the modulations of its metabolism has important physiological implications for the resistance strategies used by wild populations of this plant. As mentioned above, the fragment at m/z 96.055 retrieved in the idMS/MS for m/z 347 corresponded to the mass shift and likely the biochemical transformation between N-caffeoylputrescine and the unknown at m/z 347.196.…”
Section: Navigating the Idms/ms Molecular Network Facilitates Structumentioning
confidence: 99%
See 1 more Smart Citation